THE RELATIONSHIP BETWEEN INFORMATION ASYMMETRY AND REAL EARNINGS MANAGEMENT : THE MODERATING ROLE OF ORGANISATIONAL LIFE CYCLE - Mother. Emad Saleh Nehme; Marwa Maad Muhammad (Scholar Express Journals, 2023)
The research aims to test the effect of information asymmetry in real earning management In light of the different stages of the organisational life cycle in the Iraqi industrial companies sector, the research dealt with the concept of information asymmetry, the concept of real earning management and its impact on the company's operations as well as addressing the concept of the organisational life cycle and the relationship between information asymmetry and real earning management, and the relationship between information asymmetry and real earning management under the organisational life cycle this was done according to a sample of industrial companies listed on the Iraq Stock Exchange during the period from 2010-2019, the research reached a set of results, the most important of which were: the concept of information asymmetry is gaining a lot of attention depending on the scale of predictions of financial analysts, real earning management also includes a series of decisions to direct business activities to achieve certain objectives to influence the decisions of users of financial reports, this is according to a series of stages through which the company and the existence of discrepancies in the relationship between information asymmetry and real earning management in light of the different stages of the organisational life cycle.
Keywords: information asymmetry; real earnings management; organisational life cycle